Isolation, Identification and Comparative Study of Fungal and Bacterial Strains Found in Organic and Inorganic Soils of Different Agricultural Fields - Amir Khan2*, Fouzia Ishaq1 and (Recent Research in Science and Technology, 2011)
Soil microbial communities are arguably the most diverse communities on earth and soil represents a favorable habitat for microorganisms. Microorganisms are found in prominent amount with great species diversity in the soil of the earth. In the present investigation the extent of the diversity of microorganisms in organic soil was seen enormous comparatively in Inorganic soil. This wide range of microorganisms is also involved in important soil functions. The development and application of methods to explore microbial diversity in organic and Inorganic soil has revealed that a remarkable diversity of microorganisms were found in organic soil as compared to Inorganic soil. The reason for this was that the organic soil nourished with organic matter (manures) provided an important habitat for microorganisms. The results so far showed that the abundance of different microbial groups and total microbial biomass was generally increased by organic matters in comparison to inorganic fertilizers. It was found that with organic manures was rich in bacterial diversity (859 colonies), fungal diversity (130 colonies) and other number of microorganisms. However species richness was higher in fungi as eighteen genera comprising of 39 species and 7 genera comprising of 8 species of bacteria and has found that the organic soil was highly diverse than inorganic soil. Thus organic fertilizers have changed soil microbial community structure and we propose the fact that the soil treated with organic fertilizers is the key factor determining that soil microbial diversity is related to the complexity of the microbial interactions in soil, including interactions between microorganisms and soil, and microorganisms and plants. From the present study we thus conclude that microbial diversity of organic soil is greater and higher as compared to inorganic soil.